From Ritual Protection to Public Sociability: Meaning Transformation in Mempawah’s Robo-Robo Tradition - Tasur, Ahmad; Syahbudi; Prasojo, Zaenuddin Hudi (JOM, 2025)
This study aims to analyze the transformation of meaning in the Robo-robo tradition of the Mempawah community, from an initial orientation toward “village safety” through prayers and ritual processions into a broader social meaning that includes community interaction, entertainment, and the economic activation of micro, small, and medium enterprises (MSMEs). The research employed a qualitative approach with ethnographic orientation, using participatory observation, in-depth interviews, focus group discussions (FGDs), and visual documentation as the main techniques of data collection. The findings show that Robo-robo is attended not only as a ritual obligation but also as a social arena for networking, collective leisure, and economic exchange, particularly through MSME participation during the event. Although the core ritual elements remain performed, their significance has shifted and expanded, becoming more adaptive to contemporary socio-economic needs. Theoretically, this study implies that tradition should not be understood as a fixed cultural residue, but as a living social institution capable of refunctionalizing ritual practices into multi-purpose public spaces where sacred legitimacy, social cohesion, and economic productivity coexist and reinforce one another.